Zebrafish Models for Ectopic Mineralization Disorders: Practical Issues from Morpholino Design to Post-Injection Observations - Hosen, Mohammad J.; Vanakker, Olivier M.; Willaert, Andy; Huysseune, Ann; Coucke, Paul; De Paepe, Anne (Frontiers in Genetics, 2013)
Zebrafish (ZF, Danio rerio) has emerged as an important and popular model species to study different human diseases. Key regulators of skeletal development and calcium metabolism are highly conserved between mammals and zebrafish. The corresponding orthologs share significant sequence similarities and an overlap in expression patterns when compared to mammals, making ZF a potential model for the study of mineralization related disorders and soft tissue mineralization. To characterize the function of early mineralization-related genes in ZF, these genes can be knocked down by injecting morpholinos (MOs) into early stage embryos. Validation of the MO needs to be performed and the concern of aspecific effects can be addressed by applying one or more independent techniques to knock down the gene of interest. Post-injection assessment of early mineralization defects can be done using general light microscopy, calcein staining, Alizarin red staining, Alizarin red-Alcian blue double staining and by the use of transgenic lines. Examination of general molecular defects can be done by performing protein and gene expression analysis, and more specific processes can be explored by investigating ectopic mineralization related mechanisms such as apoptosis and mitochondrial dysfunction. In this paper, we will discuss all details about the aforementioned techniques; shared knowledge will be very useful for the future investigation of zebrafish models for ectopic mineralization disorders and to understand the underlying pathways involved in soft tissue calcification.